Caracterización y frecuencia de cataratas en perros en Medellín, Colombia (2019-2020) - Correa, Johanna (2021)
The aim of this study was to report the frequency and characterization of cataracts diagnosed in dogs that attended consultation at the Ocularvet Ophthalmological Unit, in the city of Medellín (Antioquia, Colombia) between August 2019 and August 2020. A sampling was carried out at convenience, with the inclusion of dogs of all ages with a diagnosis of cataract and the exclusion of those with previous treatments or with pathologies that make it difficult to evaluate the lens. The population was demographically characterized (breed, sex, age, previous / concomitant diseases), in addition to information related to cataract (affected eye, cataract location, degree of development). An ophthalmological evaluation was performed on 442 dogs during the study year, of which 36% were diagnosed with cataracts, representing 203 affected eyes. Male dogs (54.1%), Poodle (11.9%), Schnauzer (10.1%) and crossbreds (8.2%) were mainly affected. The frequency of cases between the age groups before 3 years of age was similar and increased after 7 years. Ten of the 159 patients (6.3%) had previous or concomitant diseases at the time of cataract diagnosis, the most frequent being type I diabetes mellitus (2.5%). The nuclear location (23.2%) was the most frequent. Likewise, the degree of incipient development (44.3%) and mature cataract (30.5%) were the most frequent. It is concluded that the degree of incipient development was the most common form of cataract, without a defined distribution by breed, sex or age